Development of elementary science learning device based on the KKNI curriculum review project based - Siti Salihah; Istiqamah Istiqamah; Nurul Himmah; Meyninda Destiara (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Development research is carried out to produce valid project-based Student Worksheets (LKM) from experts. The type of research used is research and development (Research and development or R&D) and the development model used is adapting from the Borg & Gall model stage which is limited to the fourth stage, namely 1. Information Gathering, 2. Planning, 3. Product Design, 4. Validation Test by Experts and Product Revision. The results of material expert validation with an average presentation of 82.1%, with a fairly valid category with minor revisions, because there are several suggestions and inputs from the validator that need to be revised slightly. The components of the validation aspect by media expert validation consist of 3 components, namely: presentation of material, content and completeness of presentation. The results of the media expert validation with an average presentation of 81.2% with a fairly valid category but with minor revisions according to input from media experts. The components of the media expert validation aspect consist of 2 components, namely the feasibility of display and presentation.Abstrak Penelitian pengembangan dilaksanakan untuk menghasilkan Lembar Kerja Mahasiswa (LKM) berbasis project yang valid dari para ahli. Jenis Penelitian yang digunakan adalah penelitian pengembangan (Research and development atau R&D) dan model pengembangan yang digunakan yaitu mengadaptasi dari tahap model Borg & Gall yang dibatasi hingga tahapan keempat yaitu 1. Pengumpulan Informasi, 2. Perencanaan, 3. Desain Produk, 4. Uji Validasi Oleh Pakar dan Revisi Produk. Hasil validasi ahli materi dengan rata-rata presentasi 82,1%, dengan katagori cukup valid dengan revisi kecil, karena ada beberapa saran dan masukan dari validator yang perlu direvisi sedikit. Adapun komponen aspek validasi oleh validasi ahli media terdiri dari atas 3 komponen yaitu: penyajian materi, isi dan kelengkapan penyajian. Hasil validasi ahli media dengan rata-rata presentasi 81, 2% dengan katergori cukup vali namun dengan revisi kecil sesuai masukan dari ahli media. Adapun komponen aspek validasi ahli media terdiri atas 2 komponen yaitu kelayakan tampilan dan penyajian.